Design and Mentoring PartnersiIn Improving the Sustainability of Sea Grape Products - Sulkifli, Sulkifli; Walinono , Andi Rusdi; Natsir, Andi Baso Adil; Ramadhan, Fajar; Ramadani, Wilda; Islam, Nasyfa Sahwatul (Yayasan Meira Visi Persada, 2024)
Coastal communities have not been able to fully manage and utilize environmental resources in a sustainable and sustainable manner, as well as the lack of good and directed cooperation between stakeholders. The approach used in this activity includes Technology Transfer and active participation involving partners. The form of activities provided to partners is the design of sea grape cultivation media and regular and sustainable partner assistance. The results of this community service activity succeeded in making a significant contribution in increasing the empowerment of partners both through the design of ex-situ sea grape cultivation media designed in an appropriate manner. Other results obtained in mentoring the application of good sea grape cultivation techniques that provide additional knowledge and skills to partners in managing and producing high-quality sea grape products according to market standards and provide sustainable production increases.